2008
DOI: 10.1111/j.1467-7687.2008.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers’ sensitivity to referential ambiguity: evidence for a dissociation between implicit understanding and explicit behavior

Abstract: Four-year-olds were asked to assess an adult listener's knowledge of the location of a hidden sticker after the listener was provided an ambiguous or unambiguous description of the sticker location. When preschoolers possessed private knowledge about the sticker location, the location they chose indicated that they judged a description to be unambiguous even when the message was ambiguous from the listener's perspective. However, measures of implicit awareness (response latencies and eye movement measures) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
40
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 40 publications
10
40
1
Order By: Relevance
“…These spontaneous adjustments provided a sensitive index for quantifying inter-individual differences in communicative abilities close to the onset of those abilities. This sensitivity might arise from the implicit nature of the index of audience design used in this study, in line with findings previously obtained during language comprehension in children of similar age (Nilsen & Graham, 2012;Nilsen, Graham, Smith, & Chambers, 2008). Namely, in contrast to previous work 1 9 2 | C h a p t e r 5 .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These spontaneous adjustments provided a sensitive index for quantifying inter-individual differences in communicative abilities close to the onset of those abilities. This sensitivity might arise from the implicit nature of the index of audience design used in this study, in line with findings previously obtained during language comprehension in children of similar age (Nilsen & Graham, 2012;Nilsen, Graham, Smith, & Chambers, 2008). Namely, in contrast to previous work 1 9 2 | C h a p t e r 5 .…”
Section: Discussioncontrasting
confidence: 56%
“…Differences in outcome measures might also play a role, e.g. implicit measures of knowledge about a communicative interaction (as gathered through eye movements, reaction time, or movement times) vs. explicit verbal reports requiring a degree of executive control (Nilsen, et al, 2008;Rubio-Fernandez & Geurts, 2013).…”
mentioning
confidence: 99%
“…Nilsen et al, 2008). Studies from the language learning literature suggest that sensitivity to ambiguity is present well before age 3, and in some simple cases by 13 months (Vaish et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Eye gaze measures place very low task demands on children and provide ecologically valid insights into the moment-to-moment processes underlying the comprehension of language (Fernald, Zangl, Portillo, & Marchman, 2008). In addition, recent research has demonstrated that preschoolers often show evidence of certain referential communication abilities in eye gaze measures prior to demonstrating the abilities in their overt decisions (Berman et al, 2010;Nilsen & Graham, in press;Nilsen et al, 2008).…”
Section: Codingmentioning
confidence: 98%
“…A number of studies have demonstrated that children as old as 6 years can have difficulty in expressing explicit awareness of message ambiguity both when making referential decisions and when evaluating message clarity (e.g., Beal & Flavell, 1982;Bearison & Levey, 1977;Beck, Robinson, & Freeth, 2008). However, studies that have employed highly sensitive measures, such as response latencies and eye gaze measures, have demonstrated that sensitivity to ambiguity emerges earlier during the preschool years (Matthews, Lieven, Theakston, & Tomasello, 2007;Nadig & Sedivy, 2002;Nilsen & Graham, 2009;Nilsen, Graham, Smith, & Chambers, 2008;O'Neill, 1996;Plumert, 1996). For example, 4-year-olds show an implicit appreciation for spatial ambiguity (Plumert, 1996) and can detect ambiguity in contexts where a child is a third party to a communicative exchange (Nilsen & Graham, in press;Nilsen et al, 2008) despite the fact that their explicit responses might not reflect these capabilities.…”
Section: Introductionmentioning
confidence: 97%